Discovery of potent antivirals against amantadine-resistant influenza A viruses by targeting the M2-S31N proton channel - Li, Fang (ACS Infect Dis, 2016)
Despite the existence of flu vaccines and small molecule antiviral drugs, influenza virus infection remains a public health concern that warrants immediate attention. As resistance to the only orally bioavailable drug, oseltamivir, has been continuously reported, there is a clear need to develop the next-generation of anti-influenza drugs. We chose the influenza A virus M2-S31N mutant proton channel as the drug target to address this need as it is one of the most conserved viral proteins and persist in more than 95% of currently circulating influenza A viruses. In this study, we report the development of a late-stage diversification strategy for the expeditious synthesis of M2-S31N inhibitors. The channel blockage and antiviral activity of the synthesized compounds were tested in two-electrode voltage clamp assays and antiviral assays, respectively. Several M2-S31N inhibitors were identified to have potent M2-S31N channel blockage and micromolar antiviral efficacy against several M2-S31N containing influenza A viruses.